New Distribution and Host Record of Demonax balyi (Pascoe, 1859) (Cerambycidae : Clytini) from Garhwal Region of Uttarakhand, India - Rao, Ankita; Singh, Arun Pratap; Tripathy, Ashirwad (Indian Forester, 2024)
No Abstract.